Applying Milgram’s Theory and Health Belief Model in Understanding Compliance to Health Protocols of Covid-19 Pandemic - Ernawaty, Ernawaty; Rochmah, Thinni Nurul; Afro, Rahmafika Cinthya; Dewi, Maya Sari; Wulandari, Anggun (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
COVID19 pandemic has significantly changed the world and human's normal life into a new normal life. World Health Organization had recommended early in the pandemic for the people to wear a face mask, keep a distance at a minimum of 1 meter between individuals and practice frequent handwashing with soap. Compliance with health protocols in the COVID-19 pandemic may be influenced by external factors and internal factors i.e., individual perception, knowledge, attitude, beliefs and intentions. This study aimed to compare Milgram's compliance theory and HBM concerning the community’s compliance to the health protocols of COVID-19 prevention. An online survey for a cross-sectional study had been conducted among the community in East Java province in 2020 which had obtained a total of   350 respondents. The results showed some internal factors in Milgram Theory such as region status, personal responsibility, support between communities, and relationship of heads of villages with the community had significantly influenced compliance to health protocols. Meanwhile, internal factors in HBM Theory which include perceived benefits, perceived barriers, self-efficacy, and cues to action had also a significant influence on the community’s compliance with health protocols. The internal factors in HBM Theory were more influential on the community's compliance compared to the external factors in Milgram Theory. Based on this, the government and other related parties who are responsible for improving community awareness and understanding on the need to comply with health protocols could apply the internal factors as stipulated in the HBM. The community awareness on the internal factors could also be a success factor in declining the case fatality rate (CFR) from Covid 19 infection.